Budget System Reform in Emerging Economies : The Challenges and the Reform Agenda - Diamond, Jack. (Washington, D.C. : International Monetary Fund, 2006)
With increasing frequency, the IMF has assisted middle-income countries, especially emerging economies, in adopting the types of budget reforms that have been introduced in many Organization for Economic Cooperation and Development (OECD) countries - reforms that emphasize performance and results achieved from the use of public resources. This paper examines the experience of OECD countries in introducing such reforms and assesses whether the same reform strategy be applied to non-OECD countries. It examines how emerging economies should begin such reforms, and how they should be sequenced thereafter. Based on a thorough review of the technical assistance provided by the IMF's Fiscal Affairs Department (FAD) to middle-income countries, this paper will be useful to policymakers and administrators in emerging economies who are contemplating such reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet